MENINGKATKAN KESADARAN KEWAJIBAN MELAPORKAN SPT TAHUNAN MELALUI ASISTESI PENGISIAN SPT E-FILING - Susanto, Troy Washington; Lukman, Hendro (Jurnal Serina Abdimas, 2024)
Submitting an Annual Tax Return (SPT) is an obligation for every taxpayer, however compliance is still a big challenge for taxpayers, especially individual taxpayers (WPOP). Factors that influence taxpayer awareness include the level of education, understanding of tax regulations, and the taxpayer's experience in carrying out their obligations. The aim of this Community Service Activity (PKM) is to increase tax awareness, especially reporting obligations through assistance in filling out SPT on the e-filing system. Activities carried out at the Tambora Tax Service Office. The service provided is to provide assistance to Individual Taxpayers (WPOP) along with providing awareness of the importance of tax reporting for individual and state WPOP. With this activity, it is hoped that the WPOP served will be aware of filling in the correct SPT report to be able to safeguard the interests of the WPOP themselves, and for the state in planning economy. This activity should be carried out every year to increase the level of WPOP awareness regarding tax obligations for the benefit of WPOP itself and the country ABSTRAK Penyampaian Surat Pemberitahuan Tahuanan (SPT) merupakan kewajiban bagi setiap wajib pajak, namun kepatuhannya masih menjadi tantangan besar bagi Wajib pajak, khususnya Wajib Pajak Orang Pribadi (WPOP). Faktor yang mempengaruhi kesadaran wajib pajak antara lain tingkat pendidikan, pemahaman peraturan perpajakan, dan pengalaman wajib pajak untuk melaksanakan kewajibannya. Tujuan Kegiatan Pengabdian Kepada Masyarakat (PKM) ini adalah meningkatkan kesadaran pajak khususnya kewajiban pelaporan melalui asistensi pengisian SPT pada sistem e-filing. Kegiatan yang dilakukan di Kantor Pelayanan Pajak Tambora. Pelayanan diberikan adalah memberikan asistensi Wajib Pajak Orang Pribadi (WPOP) bersamaan dengan memberikan kesadaran pentingnya palaporan pajak bagi WPOP pribadi dan negara.Dengan kegiatan ini diharapkan WPOP yang dilayani menyadari megisi laporan SPT yang benar untuk dapat mengamankan kepentingan WPOP sendiri, dan bagi negara dalam perencanaan perekonomian. Kegiatan ini sebaiknya dapat dilaksanakan setiap tahunnya agar meningkatnya tingkat kesadaran WPOP mengenai kewajiban perpajakan untuk kepentingan WPOP sendiri dan negara.